2001
DOI: 10.1002/1097-4628(20010411)80:2<207::aid-app1088>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Noble metal ion sorption by pyridyl and bipyridyl group-containing chelating polymers

Abstract: A series of eighteen 4‐vinylpyridine and 4‐methyl‐4′‐vinylbipyridine copolymers with different crosslinkers was examined as sorbents for the noble metal ions of Ag(I), Au(III), Pd(II), and Pt(II) from aqueous solutions. The chelating polymers possess appreciable sorption selectivity for Au(III) over Ag(I) and for Pd(II) over Pt(II). Binding abilities of the copolymers toward the noble metal ions vary as the identity of the chelating heterocyclic amine moiety and the structure of the crosslinkers are altered. ©… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 12 publications
0
17
0
1
Order By: Relevance
“…The use of polymer-based adsorbents for precious metal adsorption has been reported. [23][24][25] It has been shown that polymeric extractants containing heterocyclic amine units adsorb Pt 21 and Pd 21 efficiently from aqueous solutions. 25 The majorities of these studies, however, have been conducted under strongly acidic conditions (pH v 1) and a long equilibrium time has been involved (y24 h).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of polymer-based adsorbents for precious metal adsorption has been reported. [23][24][25] It has been shown that polymeric extractants containing heterocyclic amine units adsorb Pt 21 and Pd 21 efficiently from aqueous solutions. 25 The majorities of these studies, however, have been conducted under strongly acidic conditions (pH v 1) and a long equilibrium time has been involved (y24 h).…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25] It has been shown that polymeric extractants containing heterocyclic amine units adsorb Pt 21 and Pd 21 efficiently from aqueous solutions. 25 The majorities of these studies, however, have been conducted under strongly acidic conditions (pH v 1) and a long equilibrium time has been involved (y24 h). Moreover, the recovery of precious metal ions adsorbed on the polymeric adsorbents is difficult in that desorption has been conducted by either adding toxic desorption agents or destruction of polymeric adsorbents.…”
Section: Introductionmentioning
confidence: 99%
“…New publications on Au and PGM ions are regularly appearing [82,89,[97][98][99][100][101][102]. Noble metals are most often sorbed as their chloride complexes and (rarer) as bromide complexes [97].…”
Section: N-containing Sorbents For Preconcentration Of Au Pd and Ptmentioning
confidence: 99%
“…In some cases, they cannot distinguish between oxidation states of platinum, Pt(II) and Pt(IV), when both are present in solution. Selective sorption of only Pt(II) has been reported [], hence under suitable conditions, the ions of Pt(II) and Pt(IV) [] or Pt and Pd [] could be selectively separated and enriched.…”
Section: Sorbentsmentioning
confidence: 99%
“…Сорбцию проводили во фталатном буфере (рН 4,01) в течение 12 ч при 22 °С с перемешиванием [4]. Полученные максимальные сорбци-онные ёмкости (СЕ) по Pt 2+ и Pd 2+ для Thio-SBA-15 сравнимы с СЕ полимерных сорбентов [5][6][7]. 12,5).…”
Section: Introductionunclassified